Determinan Ketimpangan Distribusi Pendapatan Kabupaten/Kota di Provinsi Bali - I Kadek Surya Ade Wirawan; I Nyoman Mahaendra Yasa (BADAN PENERBIT STIEPARI PRESS, 2026)
Income distribution inequality continues to be a significant socio-economic challenge in Bali Province, potentially limiting overall community welfare and sustainable development. This study investigates the impact of education level, labor force participation, district/city minimum wage, and government capital expenditure on income distribution inequality across 9 districts and cities in Bali Province over the period 2014–2024, using a total of 99 observations. Employing panel data regression analysis with the Random Effects Model, the results indicate that all four variables, both simultaneously and individually, have a negative and statistically significant effect on income distribution inequality. Specifically, higher education levels and increased labor force participation are associated with a reduction in inequality, while higher minimum wages and more efficient allocation of capital expenditure further contribute to narrowing income disparities. These findings are consistent with the Human Capital Theory and the Kuznets hypothesis, emphasizing the role of investment in human resources and economic policies in shaping equitable growth. The study provides actionable policy recommendations for the Bali Provincial Government, suggesting enhanced access to education, labor market optimization, strategic minimum wage adjustments, and targeted capital expenditure to effectively reduce income inequality in the region.